Dynamic Difficulty Adjustment (DDA) in Computer Games: A Review. (1st November 2018) - Zohaib, Mohammad
Abstract : Dynamic difficulty adjustment (DDA) is a method of automatically modifying a game's features, behaviors, and scenarios in real-time, depending on the player's skill, so that the player, when the game is very simple, does not feel bored or frustrated, when it is very difficult. The intent of the DDA is to keep the player engrossed till the end and to provide him/her with a challenging experience. In traditional games, difficulty levels increase linearly or stepwise during the course of the game. The features such as frequency, starting levels, or rates can be set only at the beginning of the game by choosing a level of difficulty. This can, however, result in a negative experience for players as they try to map a predecided learning curve. DDA attempts to solve this problem by presenting a customized solution for the gamers. This paper provides a review of the current approaches to DDA.